The 26th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2004.1403686
|View full text |Cite
|
Sign up to set email alerts
|

Measuring bioimpedance in the human uterine cervix: towards early detection of preterm labor

Abstract: We have created a bioimpedance probe designed to detect subtle changes in human cervical tissue composition in vivo, and thereby detect the onset of cervical remodeling in a noninvasive manner sooner than existing clinical methods allow. Our cervical bioimpedance measurement device, which can be used during a routine pelvic examination, is composed of a contoured probe with disposable tip and, within the probe's handle, a bioimpedance sensor equipped with an integrated chip capable of generating sinusoidal vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…3 show the fluorescent excitation/emission peaks for collagen lie around 370 nm/420 nm. Changes in fluorescence counts, impedance magnitude, and impedance phase are a function of collagen concentration, and the range of values is in concordance with the literature [15], [24], [33]–[35], [39], [41]–[43], [50]–[52]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3 show the fluorescent excitation/emission peaks for collagen lie around 370 nm/420 nm. Changes in fluorescence counts, impedance magnitude, and impedance phase are a function of collagen concentration, and the range of values is in concordance with the literature [15], [24], [33]–[35], [39], [41]–[43], [50]–[52]. …”
Section: Discussionsupporting
confidence: 89%
“…The cup-like design for the tip of the intravaginal probe was a consequence of arranging electrodes on both the bottom and sides of the cup to generate spatial diversity in impedance measurements. Furthermore, whereas other researchers have used loaded-spring mechanisms in pencil-probe designs to saturate force-dependent variability in impedance measurements, we exploited the elasticity of the bulk silicone material itself via the form-fitting cup-like design to accomplish the same goal [52]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous works published in the literature (Avis et al, 1997;Etemadi et al, 2013;Gandhi et al 2006a;2006b;Hoe et al, 2004;O'Connell et al, 2000) produced results in line with those reported here. However, none of them include an equivalent circuit for the cervical tissue, as it is done here.…”
Section: Discussionsupporting
confidence: 92%
“…The former is based on the auto fluorescent properties of the collagen cross-links; and the latter is based on the electrical impedance characteristics of the cervical tissue. The use of electrical impedance to assess cervical ripening has been reported in the literature, e.g., Avis et al (1997), Etemadi et al (2013), Gandhi et al (2006a;2006b), Hoe et al (2004) andO'Connell et al (2000). Avis et al (1997) presented in-vitro measurements of the electrical impedance of cervical tissue from samples taken at caesarean sections, and reported differences between term and preterm samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation